Perancangan Sistem Monitoring Tingkat Paparan Radiasi pada Transportasi Zat Radioaktif Berbasis Mikrokontroler ATMega8 - , IMAM ANDRIAN RISOYO, I Wayan Mustika,S.T.,M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transportation of nuclear substances is one of activities in delivering radioactive substances from one location to another. Th is activity has a potential risk of radiation leakage exposure to the environment. For safety reason, dose rate of radiation substances has to be monitored during transportation. This research aims to build a prototype of dose rate monitoring system, which can measure the rate of radiation exposure, vehicle position and time. All data will be transmitted to the central station via a telecommunication network on real-time basis. The system is equipped with Global Positioning System (GPS) for data positioning and Global System for Mobile Communication (GSM) for data communication. The research is expected to provide benefit in monitoring of dose rate of radioactive substances and the position of vehicle during the transportation. Thus, if the radiation leakage can be monitored, a necessary action can be taken immediately to minimize the risk.